2015
DOI: 10.1200/jco.2013.52.9651
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Controlled Trial of the Prophylactic Effect of Urea-Based Cream on Sorafenib-Associated Hand-Foot Skin Reactions in Patients With Advanced Hepatocellular Carcinoma

Abstract: UBC prophylaxis in patients with advanced HCC starting sorafenib reduced HFSR rates, extended the time to first occurrence of HFSR, and improved patient quality of life compared with BSC. Blinded, randomized, placebo-controlled trials to determine the role of UBC on the incidence and severity of HFSR are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
110
0
8

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(121 citation statements)
references
References 30 publications
3
110
0
8
Order By: Relevance
“…Regular use of topical agents is recommended Bellmunt et al 2011]. A large randomized, controlled phase II study (N = 868) of patients with HCC treated with sorafenib demonstrated that prophylaxis with urea-based cream over a 12-week period significantly reduced the incidence of all grades of HFSR compared with best supportive care in patients treated with sorafenib (56% versus 74%; p < 0.0001) Ren et al 2012]. In another study of patients with HCC receiving sorafenib, use of a corticosteroid ointment significantly improved HFSR score, and the need for treatment modifications was reduced [Lu et al 2013].…”
Section: Case Studiesmentioning
confidence: 99%
“…Regular use of topical agents is recommended Bellmunt et al 2011]. A large randomized, controlled phase II study (N = 868) of patients with HCC treated with sorafenib demonstrated that prophylaxis with urea-based cream over a 12-week period significantly reduced the incidence of all grades of HFSR compared with best supportive care in patients treated with sorafenib (56% versus 74%; p < 0.0001) Ren et al 2012]. In another study of patients with HCC receiving sorafenib, use of a corticosteroid ointment significantly improved HFSR score, and the need for treatment modifications was reduced [Lu et al 2013].…”
Section: Case Studiesmentioning
confidence: 99%
“…Of 868 patients treated with sorafenib for hepatocellular carcinoma, a reduction was seen in the incidence of all-grade HFSR (56% in treatment arm vs. 73.6% in controls; p < 0.0001), and a 2.5-fold increase in the median time-tofirst onset of HFSR (84 days in the treatment arm vs. 34 days in controls; p < 0.001), with the preventive daily use of ureabased cream (58) . Figures 4 (55) and 5 (38) provide recommendations for the prevention of HFSR and acneiform rash respectively.…”
Section: Managementmentioning
confidence: 99%
“…Ren and coworkers confirmed superiority of urea over standard local treatment as prophylaxis of HFSR in 871 patients with hepatocellular carcinoma treated with sorafenib [12]. During the 12 week study period 56.0% of the patients in the urea arm and 73.6% of the patients in the best standard local treatment arm suffered from HFSR of any grade (p<0.001).…”
mentioning
confidence: 93%